Revision of the Siobla metallica group (Hymenoptera: Tenthredinidae) - Niu, Gengyun; Wei, Meicai; Taeger, Andreas (Zootaxa, 2012)
Twenty-two species of Siobla metallica species-group are revised. Fourteen new species: Siobla bomeica Niu & Wei, sp. nov., S. brevipilosa Niu & Wei, sp. nov., S. caerulea Niu & Wei, sp. nov., S. dian Niu & Wei, sp. nov., S. glabroorbita Niu & Wei, sp. nov., S. glabrotemporalis Niu & Wei, sp. nov., S. leucotarsis Niu & Wei, sp. nov., S. longipennis Niu & Wei, sp. nov., S. maculipennis Niu & Wei, sp. nov., S. obtusiscutellata Niu & Wei, sp. nov., S. rugosipropodea Niu & Wei, sp. nov., S. shennongjiana Niu & Wei, sp. nov., S. sinica Niu & Wei, sp. nov. and S. vardalae Niu & Wei, sp. nov. are described and illustrated. Six previously described species are redescribed. A key for species of the group is given. Distribution records of each species of the group are given.